Analysis Of Factors Affecting Student Interest In Career Selection As Public Accountant - Ni Made Wangi Juliasih; Ni Putu Sri Harta Mimba (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2024)
Data from the Center for Financial Professional Development shows that the number of public accountants in Indonesia has decreased in the last two years, while companies that need public accounting services always increase. Companies require an audit opinion on the fairness of its financial statements. The difference between this study and previous research lies in the analysis techniques and variables used. This study aims to determine the effect of Understanding Information Technology, Soft skills, Finansial Reward, and Market Consideration on student interest in becoming a public accountant. The population in this study is 256 accounting students from the 2019 class. The sample collection technique used is the purposive sampling method with 156 samples. The data analysis technique used is Partial Least Square. The results show that the understanding of information Technology has no significant effect on student interest in becoming accountant public. while Soft skills, Financial Reward, and Market Consideration have a positive effect on student interest in becoming a public accountant. The research results provide evidence of the development of TPB and the Expectancy Theory.